Study of Collection of Bank Receivables in the Commercial Code and New Bill of Commercial Code of Iran - Yektaei, Saeid (International Journal of Psychosocial Rehabilitation, 2025)
According to Article 2 of Commercial Code of Iran, banking activity is a kind of commercial transaction; therefore, banks are considered as merchants subject to applicable rules on this group. Increasing rates of overdue and deferred receivables of banks relative to total current loans in banking system are new national challenges in Iran due to bankruptcy and existing legal gap. The legal gap in this field is an extra reason that increases overdue and deferred receivables in banking system. This reason is categorized into three main groups of banks, debtors, and external factors. Therefore, it is essential to investigate the issue and its solution in order to prevent increasing outstanding claims of granted loans and collection of debts. If the abovementioned problems are solved, banking system and browsers will benefit from a suitable situation. On the other hand, there are debtors who are not able to repay loans or do not tend to pay their debts despite their financial power. In case of external factors, some crises such as domestic and international issues, the government, courts, registration rules, notary offices, and the like have doubled complexity of mutual interaction between bank and debtor. Therefore, this study examines the structure of banks, bank’s debt collection, measures taken by banks to prevent consequences of bankruptcy, and private-specialized debt collection agencies.